Internal Hernia Masquerading As Necrotizing Enterocolitis - Ranjit I. Kylat (Frontiers Media S.A., 2017)
In extremely preterm infants, acute abdominal emergencies are fortunately less common with improving care. Spontaneous intestinal perforation and necrotizing enterocolitis are conditions where emergency surgery is most often needed. Conservative medical management and placement of temporary drain are often used in the initial management. Internal hernia (IH) is an uncommon cause of bowel obstruction in neonates, is difficult to diagnose and unfortunately are found only at autopsy. The presentation in preterm infants, distinction between these conditions, and the need for early diagnosis of IH are discussed.